Building a Firm Foundation: Preparing Pre-K–4 Teachers for Integrative STEM Pedagogy - Brusic, Sharon; Marcum-Dietrich, Nanette; Shettel, Jennifer; White, Janet (Innovations in Science Teacher Education, 2023)
Preservice teachers in early childhood (pre-K–4) education teacher preparation programs typically experience content-specific pedagogy courses that operate in isolation from each other. In addition, preservice teachers are rarely given the opportunity to learn about integrative teaching in science, technology, engineering, and mathematics (STEM). In this article, the authors describe how Millersville University of Pennsylvania, a midsized regional public university in the Mid-Atlantic Region, addressed this issue in their teacher preparation program by creating an integrative STEM (iSTEM) minor that provided preservice teachers with five additional courses that explored how to implement STEM in early childhood classrooms in developmentally appropriate ways with a design-based pedagogy. This article introduces the program, including the specific coursework that preservice teachers engage in as well as other programmatic features that contribute to the success of the minor in increasing the confidence and skill levels of future teachers in successful STEM integration techniques. Photographs and artifacts are included to provide readers with a clearer picture of the types of learning activities and assignments in which students engaged. The article concludes with qualitative comments from students who participated in this program.